Modelling of blood glucose metabolism using neural networks with online learning - Siti Nadiah Zainal. (2010)
Diabetes is a disease caused by the lack of the hormone insulin, which is responsible for regulating the amount of glucose in the blood. Diabetic patients undergo treatment by injecting insulin into their bloodstream after meals, and the difficulty is often in estimating the amount of insulin needed. An overdose of insulin may lead to fatal consequences, as the patients may find a complete lack of blood glucose for their basic cell metabolism. This project attempts to develop a neural model of the glucose cycle for analysis and prediction of effects of disturbance in the form of food intake as well as energy consuming through exercise. Subsequently, this model will be used to control the amount of insulin to be given to the patients.